The Fox Busters - "King, smith Dick" (Puffin Books: London, 1995)
A community of chickens continually preyed on by hungry foxes is saved by the birth of three wonder chicks, who grow into magnificent flying machines and lead a climatic barnyard battle
Keywords: Chickens Fiction